Economic complexity and corporate governance. Issue 1 (2nd January 2022) - Barros, Fernando; Brotherhood, Luiz; Rodrigues, Victor
ABSTRACT: Using dynamic panel data techniques, we find that a country's corporate governance practices have a positive effect on the sophistication of its exported products. We also find that higher dispersion of governance across firms leads to lower economic complexity.